Research Pearls: The Significance of Statistics and Perils of Pooling. Part 3: Pearls and Pitfalls of Meta-analyses and Systematic Reviews - Harris, Joshua D; Brand, Jefferson C; Cote, Mark P; Dhawan, Aman (Arthroscopy, 2017)
Within the health care environment, there has been a recent and appropriate trend towards emphasizing the value of care provision. Reduced cost and higher quality improve the value of care. Quality is a challenging, heterogeneous, variably defined concept. At the core of quality is the patient's outcome, quantified by a vast assortment of subjective and objective outcome measures. There has been a recent evolution towards evidence-based medicine in health care, clearly elucidating the role of high-quality evidence across groups of patients and studies. Synthetic studies, such as systematic reviews and meta-analyses, are at the top of the evidence-based medicine hierarchy. Thus, these investigations may be the best potential source of guiding diagnostic, therapeutic, prognostic, and economic medical decision making. Systematic reviews critically appraise and synthesize the best available evidence to provide a conclusion statement (a "take-home point") in response to a specific answerable clinical question. A meta-analysis uses statistical methods to quantitatively combine data from single studies. Meta-analyses should be performed with high methodological quality homogenous studies (Level I or II) or evidence randomized studies, to minimize confounding variable bias. When it is known that the literature is inadequate or a recent systematic review has already been performed with a demonstration of insufficient data, then a new systematic review does not add anything meaningful to the literature. PROSPERO registration and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines assist authors in the design and conduct of systematic reviews and should always be used. Complete transparency of the conduct of the review permits reproducibility and improves fidelity of the conclusions. Pooling of data from overly dissimilar investigations should be avoided. This particularly applies to Level IV evidence, that is, noncomparative investigations. With proper technique, systematic reviews and meta-analyses have the potential to be powerful investigations that efficiently assist clinicians in decision making.